INVESTIGATING LANGUAGE LEARNERS’ EMOTION REGULATION STRATEGIES VIA ACHIEVEMENT EMOTIONS IN LANGUAGE LEARNING CONTEXTS - Yildirim, Cihan; Atay, Derin (TEFLIN Journal, 2024)
This study investigates the role of emotion regulation strategies on achievement emotions among tertiary-level English as a Foreign Language (EFL) students. It also explores the strategies employed by students to regulate these emotions. Employing a mixed-method sequential explanatory design, data was collected from forty-nine language learners attending prep-classes at the Department of Foreign Languages in a state university in Türkiye. The participants were categorized based on their utilization of cognitive reappraisal (CR), expressive suppression (ES), or a combination of both emotion regulation strategies (ERSs). They completed the Emotion Regulation Questionnaire and the Academic Emotions Questionnaire-Foreign Language Classroom to assess differences in achievement emotions among groups. Subsequently, the participants provided narratives regarding their perceptions and regulation of emotions. Thematic analysis using MAXQDA (Version 2020) was conducted. Results revealed significant variations in emotions among groups, with the ES group reporting lower levels of positive emotions and higher levels of negative emotions compared to others. The study underscores the importance of evaluating emotion regulation strategies to foster sustainable and enjoyable language learning environments.